A Patient with Combined CADASIL and MTHFR Homozygosity. (17th February 2020) - Ibrikji, Sidonie; El Halabi, Tarek; Yamout, Bassem
Abstract : Cerebral Autosomal Dominant Arteriopathy with Subcortical Infarcts and Leukoencephalopathy (CADASIL) is an inherited disorder caused by a mutation in the NOTCH 3 gene, characterized by early onset of subcortical lacunar infarcts in the absence of vascular risk factors and cerebral microbleeds. Homozygosity for the factor Methylenetetrahydrofolate Reductase (MTHFR) is also associated with lacunar stroke risk and cerebral small-vessel disease regardless of the homocysteine level. The coexistence of MTHFR C677T homozygosity and NOTCH 3 mutation has never been reported in the literature previously, and that brings up the challenge of antithrombotic treatment in the presence of cerebral microbleeds.